Southern Vietnamese women’s views on HPV vaccination, cervical cancer screening, and HPV self-sampling - Minh Tung Phung; Pham Le An; Lilah Khoja; Alice W. Lee; Celeste Leigh Pearce (Scientific Reports)
Abstract Cervical cancer remains a significant public health issue in Vietnam, particularly in the South where the incidence is double the national average. However, HPV vaccination and cervical cancer screening uptake remains low in this region. This study explored Southern Vietnamese women’s views on cervical cancer prevention, including HPV self-sampling, a World Health Organization-endorsed screening method. In October-November 2021, six focus groups were conducted with 44 women aged 30–65. A trained researcher who was a native Vietnamese speaker moderated the discussions using a semi-structured guide covering knowledge and attitudes toward cervical cancer prevention. Participants also watched videos on screening methods and shared their views. Discussions were audio-recorded, transcribed, translated to English, and thematically analyzed using Dedoose 9.0.46. Three main themes emerged: (1) barriers to prevention included low knowledge, logistical and psychological challenges, and issues related to healthcare providers; (2) participants viewed HPV self-sampling positively, although concerns about incorrect self-sampling and mailing logistics were noted; (3) participants generally accepted cervical cancer prevention and drew parallels to COVID-19 prevention, suggesting similar public health approaches. These findings suggest that combining HPV self-sampling with strategies used for COVID-19 prevention, including public education, government support, and improved access, could enhance cervical cancer prevention in Southern Vietnam.